Hubungan Umur, Masa Kerja, Pengetahuan dan Sikap Operator Mesin Winding Unit Spinning VI dengan Kepatuhan dalam Pemakaian Masker Kain di Industri Tekstil Semarang - Hartati, Sri; Kurniawan, Bina; -, ekawati (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2011)
Safety behaviour becomes a major factor for the achievement of zerro accident (no accident). Person’s behaviour was influenced by predisposing, enabling and reinforcing factors. Predisposing factors is an antecedent to behavioral factors that are the basis or motivation for behaviour. One of the safety behaviour is compliance, especially compliance using personal protective equipment; for example using cloth mask must be obeyed by all workers. This study aims to determine the relationship between age, length of work, knowledge and attittudes of workers with compliance in using cloth mask. The research design used cross sectional methode in which the dependent variables investigated at the same time. The poppulation was all winding machine operators in spinning unit VI at a Semarang textile industry. The sample consist of 44 respondents that taken by non random sampling methode. The Chi square test used here and the result showed that there was no correlation between age (p=0,322) ang length of work (p=0,731) with compliance using cloth masks. There were correlation between knowledge (p=0,019) and attitude (p=0,030) of workers with compliance in using cloth masks. It is suggested to hold the safety talk, training, counseling and supervision to increase the compliance in using cloth masks.